2005
DOI: 10.18388/abp.2005_3447
|View full text |Cite
|
Sign up to set email alerts
|

Direct tumor damage mechanisms of photodynamic therapy.

Abstract: Photodynamic therapy (PDT) is a clinically approved and rapidly developing cancer treatment regimen. It is a minimally invasive two-stage procedure that requires administration of a photosensitizing agent followed by illumination of the tumor with visible light usually generated by laser sources. A third component of PDT is molecular oxygen which is required for the most effective antitumor effects. In the presence of the latter, light of an appropriate wavelength excites the photosensitizer thereby producing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
118
0
19

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(139 citation statements)
references
References 119 publications
2
118
0
19
Order By: Relevance
“…The increase in green fluorescence indicates ROS formation near or in the nucleus and mitochondria. This notion may be of importance when deciphering the underlying signaling events and pathways of ZnPc-PDT in terms of apoptosis (38). nucleus and mitochondria specific ROS formation was partially blocked by pre-incubation with the antioxidant vitamin C, supporting the idea that ROS formation may be of particular importance for the antiproliferative effects of the novel photosensitizer.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The increase in green fluorescence indicates ROS formation near or in the nucleus and mitochondria. This notion may be of importance when deciphering the underlying signaling events and pathways of ZnPc-PDT in terms of apoptosis (38). nucleus and mitochondria specific ROS formation was partially blocked by pre-incubation with the antioxidant vitamin C, supporting the idea that ROS formation may be of particular importance for the antiproliferative effects of the novel photosensitizer.…”
Section: Discussionmentioning
confidence: 75%
“…Importantly, an increase in cytochrome c was detected. Together with the marked increase in caspase-3 activity, the data indicated that ZnPc-PDT induces a mitochondria-dependent, intrinsic induction of apoptosis in esophageal cancer cells (38).…”
Section: Discussionmentioning
confidence: 82%
“…The results obtained in this study demonstrated that the 405 and the 460 nm LED systems produced considerable inactivation in most cases, while the 520 nm LED did not lead to any significant inactivation (P > 0Á05) in the populations of the three bacteria. Photodynamic inactivation by visible light depends on the absorption spectrum of a special class of compounds called photosensitizers (Nowis et al 2005). Endogenous photosensitizers such as porphyrins have a characteristic absorption band between 400 and 430 nm (Redi and Jori 1988) and photodynamic inactivation occurs when light of wavelength between 400 and 500 nm is absorbed (Maclean et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The first study to report apoptosis following PDT was carried out by Agarwal et al (1991) in mouse lymphoma L5178Y cells sensitized by chloroaluminium phthalocyanine. Since then, numerous studies have shown apoptosis to be a prominent type of cell death in PDT (Kessel and Luo, 1998;Srivastava et al, 2001;Agostinis et al, 2004;Nowis et al, 2005). PDT induces apoptosis by two major pathways: intrinsic pathway or mitochondria-mediated apoptosis and extrinsic pathway or death receptor-mediated apoptosis (Almeida et al, 2004).…”
Section: Mechanisms Involved In Topical Pdtmentioning
confidence: 99%